Genotypic Variations in Ferulic Acid, Antioxidant Capacity and Yield Components of Thai Landrace Rice Genotypes - Chayut Srihanoo; Chorkaew Aninbon; Nittaya Phakamas (AGRIVITA, Journal of Agricultural Science, 2022)
Ferulic acid is a potent antioxidant in rice. The objective of this study was to evaluate the variations in ferulic acid and antioxidant capacity among landrace rice genotypes. The experiment is conducted under paddy field conditions in two locations. It uses a randomized complete block design with three replications, and the treatments consist of 24 landrace rice genotypes. Data are collected for yield and yield components, ferulic acid, and antioxidant capacity. Rice genotypes are significantly different for plant height, number of panicles per plant, number of seeds per panicle, 1,000 - seed weight and grain yield. Grain yields of 24 rice genotypes ranged from 1,476.9 to 4,348.1 kg/ha, and G24 is a good source for high grain yield. Variations in ferulic acid content and antioxidant capacity are found among genotypes. Ferulic acid contents range from 11.56 to 45.68 mg/100 g seed, and antioxidant capacity determined by the DPPH method ranged from 15.46 to 86.26%. G6 has the highest ferulic acid content and antioxidant capacity. These two genotypes are promising for parents in breeding programs targeting improved ferulic acid content, antioxidant capacity, and yield.